Efektivitas Pelaksanaan Program Bimbingan Belajar Tambahan di Luar Jam Pelajaran dalam Mengatasi Kesulitan Belajar Siswa pada Bidang Kurikuler di Sekolah MA Kedondong - Debora Sidabutar; Linda Shovia; Lutfiah Rahmah; Nofrian Bahari; Nur Handayani; Rico Maulana Jaya; Rizkon Ali Husen; Harry Wijayanto; Arizal Eka putra (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Learning is a dynamic process involving interactions between students, educators, and learning resources in an environment designed to achieve a deep understanding of the material. One of the challenges often faced in education is learning difficulties, especially in subjects considered difficult such as Mathematics and English. Additional tutoring programs outside of class hours are a solution to help students overcome the academic difficulties they face. This study aims to evaluate the effectiveness of a tutoring program in addressing learning difficulties in Kedondong District, with a focus on Mathematics and English. This program involves students experiencing difficulty understanding the subject matter and provides intensive guidance using an interactive approach and the use of technology-based learning media, such as multimedia and educational quizzes, which make learning more engaging. The evaluation results show a significant increase in student understanding of the material, as well as positive changes in student motivation, independence, and self-confidence. This program not only successfully improves academic understanding but also fosters a higher enthusiasm for learning in students. Despite challenges, such as limited resources and differences in student understanding levels, this program is able to create a conducive learning environment. Therefore, it is hoped that this program can be replicated in other regions to improve the quality of education in a sustainable manner, by involving various parties, such as the government, educational institutions, and the community.